2018
DOI: 10.1134/s160767291801012x
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of YABBY1 and YABBY3 Genes in Lateral Organs of Tomato Species (Solanum, Section Lycopersicon)

Abstract: The interspecific polymorphism and the expression patterns of the genes encoding the YABBY1 and YABBY3 transcription factors of cultivated tomato Solanum lycopersicum and wild species S. chmielewskii, S. peruvianum, and S. habrochaites are characterized. The possibility of an inverse relationship between the level of YABBY1 and YABBY3 genes coexpression and the size of leaves and flowers of the tomato species studied is shown. The phylogeny of the genes suggests an earlier emergence of YABBY1 compared to YABBY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Previous work provided evidence that YAB2-like genes function to promote laminar outgrowth and stamen morphologic evolution [17]. Apart from conserved YAB2 regulation, the dynamic regulation and biological function of INO-like and CRC-like genes should be conserved in angiosperm plants as consistent as that in the previous findings that INO and CRC genes were involved in the seed formation and differentiation of the nectary in basal taxa, respectively [14,16,22,28,29].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previous work provided evidence that YAB2-like genes function to promote laminar outgrowth and stamen morphologic evolution [17]. Apart from conserved YAB2 regulation, the dynamic regulation and biological function of INO-like and CRC-like genes should be conserved in angiosperm plants as consistent as that in the previous findings that INO and CRC genes were involved in the seed formation and differentiation of the nectary in basal taxa, respectively [14,16,22,28,29].…”
Section: Discussionsupporting
confidence: 77%
“…Generally, CRC and INO are considered the "reproductive-specific YABBY genes", whereas FIL, YAB2, YAB3, and YAB5 are referred to as the "vegetative YABBY genes" [10,11]. Accordingly, the "vegetative YABBY genes" could regulate the lateral organ polarity development, formation of margins, maturation of the leaf, and development and phyllotaxis of the shoot apical meristem and are detected both in leaf primordia and floral organs [12][13][14], whereas two other genes, CRC and INO, are restricted to developing carpels and the outer integument of the ovule, respectively. Besides regulating carpels polarity, CRC genes are also required and essential for nectary specification [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pigment profiling presented herein revealed that yellow apples had similar levels of carotenoids but significant lower levels of chlorophylls than apples grown at other locations and showing greenish coloration (Figure 1). These observations strongly suggest that higher chlorophylls levels in greenish "Golden Reinders" apples may be shielding the carotenoid contribution to peel color as it was described in pepper (Filyushin et al, 2020). Hence, it may be that chlorophyll levels in apple peel must fall below a certain threshold for achieving an optimal yellow color as previously observed during olive ripening (Mínguez-Mosquera and Gallardo-Guerrero, 1995).…”
Section: Fernándezsupporting
confidence: 62%
“…FIL, YAB2, YAB3, and YAB5 regulate gene expression in vegetative tissues [ 19 , 20 ], including the polar development of lateral organs, the formation of edges, the maturity of leaves, and the development of shoot apical meristems and phyllodes. FIL is expressed in both leaf primordia and floral organs [ 3 , 21 , 22 ]. As a transcriptional regulator, FIL not only is involved in the formation of floral organs and leaf development [ 17 , 23 ], but also affects anthocyanin accumulation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%